A Study of Student Demographic Variables as Predictors of Intentions to Adopt Computer-Based Testing in Nursing School Clinical Examination - Bakare, Olusegun Ojo; Bolarinwa, Adebola Arike (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Despite the increasing integration of computer-based testing in nursing education, little is known about how student demographic variables influence their intentions to adopt this technology in clinical examinations. This gap in understanding may hinder effective implementation strategies and reduce student acceptance. Therefore, this study aims to determine whether a combination of nursing students’ demographic variables significantly predicts their intention to use computer-based testing (CBT) in clinical examinations; quantify the proportion of variance in students’ intentions to use CBT that is explained by their demographic data; and assess the relative contribution of each demographic variable to students' intentions to adopt CBT in clinical examinations. The study adopted a correlation research design with a population comprising all nursing schools in Osun State. The study purposively selected six nursing schools from the population. While the simple random sampling technique was used to select 20 nursing students from each school, totaling 120 respondents. A self-developed instrument was used to elicit data from the students, with an internal reliability of 0.87 obtained using Cronbach's alpha. The data collected were analyzed using multiple regression analysis. The finding showed that the combined demographic variables did not statistically and significantly predict the nursing student’s intentions to adopt CBT in their clinical exams. Only 5.6% of the variance in nursing students’ intention to use CBT in clinical examinations was explained by the combined demographic variables. However, gender significantly predicted the nursing students’ intentions to adopt CBT. It concluded that nursing students’ demographic data were not influencing their intentions to use CBT in clinical examinations. The paper outlined the implications for the study.